2021
DOI: 10.1364/oe.434024
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning wavefront sensing for fine phasing of segmented mirrors

Abstract: Segmented primary mirror provides many crucial important advantages for the construction of extra-large space telescopes. The imaging quality of this class of telescope is susceptible to phasing error between primary mirror segments. Deep learning has been widely applied in the field of optical imaging and wavefront sensing, including phasing segmented mirrors. Compared to other image-based phasing techniques, such as phase retrieval and phase diversity, deep learning has the advantage of high efficiency and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A DNN can be used to directly construct the relationship between a point map obtained by a Shack-Hartmann wavefront sensor and the calibration voltage to improve calibration efficiency [63]. Bi-GRU can be used to obtain the corresponding relationship between the defocused star images and the wavefront [64]. A sketch map of the co-phasing approach using the Bi-GRU network is shown in Figure 5.…”
Section: Mirror Surface Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…A DNN can be used to directly construct the relationship between a point map obtained by a Shack-Hartmann wavefront sensor and the calibration voltage to improve calibration efficiency [63]. Bi-GRU can be used to obtain the corresponding relationship between the defocused star images and the wavefront [64]. A sketch map of the co-phasing approach using the Bi-GRU network is shown in Figure 5.…”
Section: Mirror Surface Calibrationmentioning
confidence: 99%
“…Figure 5.In-focus and defocused star images and aberrated wavefront maps are used to train the Bi-GRU network, and the trained network is used to predict wavefront maps[64].…”
mentioning
confidence: 99%
“…The methods based on pre-calibration or iteration have problems such as being only suitable for a single scene or a large amount of calculation. In recent years, with the wide application of deep learning in various fields, optical problems are also more widely solved by deep learning, including optical interferometry [ 13 ], single-pixel imaging [ 14 , 15 ], wavefront sensing [ 16 , 17 , 18 ], remote sensing [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] and Fourier ptychography [ 27 , 28 , 29 ]. Using deep learning for image enhancement in imaging systems is also more attractive [ 22 , 23 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Xiafei Ma et al demonstrated that using only a single deep convolutional neural network (DCNN) is sufficient to detect pistons from a broadband extended image [ 10 ]. Yirui Wang et al authenticated that a Bi-GRU neural work with a much simpler structure can be effectively used for delicate phase segmented mirrors [ 11 ].…”
Section: Introductionmentioning
confidence: 99%